The Rise of Synthetic Marijuana in Turkey: The Bonzai Phenomenon of the 2010s - (:unkn) unknown (My University, 2014)
0

In the 2010s, synthetic marijuana products, mostly referred to as Bonzai, have become a critical phenomenon in the drugs realm worldwide. In Turkey and many other countries, state authorities and the public have been alarmed about the rapid widespread of these drugs. Frequent cases of death related to Bonzai use have placed these substances among the top concerns on the public's agenda. This article primarily aims to analyze the conditions and factors that have enabled Bonzai's rapid popularization among Turkish drug users. To achieve this, I have used a compilation of qualitative data received from books, articles, news sources, expert comments, official drug reports and interviews with five male ex-users living in Istanbul. From this data, certain factors contributing to the increasing popularity of Bonzai drugs in Turkey have been deduced. Furthermore, significant information related to these substances' history and the causes of death cases in Turkey have been noted from the interviewees
Keywords: Psikoloji